Alginate/Chitosan Nanoparticles are Effective for Oral Insulin Delivery - Sarmento, B. (2007)
Abstract Purpose To evaluate the pharmacological activity of insulin-loaded alginate/chitosan nanoparticles following oral dosage in diabetic rats. Methods Nanoparticles were prepared by ionotropic pre-gelation of an alginate core followed by chitosan polyelectrolyte complexation. In vivo activity was evaluated by measuring the decrease in blood glucose concentrations in streptozotocin induced, diabetic rats after oral administration and flourescein (FITC)-labelled insulin tracked by confocal microscopy. Results Nanoparticles were negatively charged and had a mean size of 750 nm, suitable for uptake within the gastrointestinal tract due to their nanosize range and mucoadhesive properties. The insulin association efficiency was over 70% and insulin was released in a pH-dependent manner under simulated gastrointestinal conditions. Orally delivered nanoparticles lowered basal serum glucose levels by more than 40% with 50 and 100 IU/kg doses sustaining hypoglycemia for over 18 h. Pharmacological availability was 6.8 and 3.4% for the 50 and 100 IU/kg doses respectively, a significant increase over 1.6%, determined for oral insulin alone in solution and over other related studies at the same dose levels. Confocal microscopic examinations of FITC-labelled insulin nanoparticles showed clear adhesion to rat intestinal epithelium, and internalization of insulin within the intestinal mucosa. Conclusion The results indicate that the encapsulation of insulin into mucoadhesive nanoparticles was a key factor in the improvement of its oral absorption and oral bioactivity.